DIVERSIFIKASI PRODUK SAGU (Metroxylon sp) DAN POLA KONSUMSI MAKANAN LOKAL MASYARAKAT ASLI PAPUA PESISIR DI KAMPUNG MAKIMI DISTRIK MAKIMI KABUPATEN NABIRE - Hans F Liborang (Jurnal FAPERTANAK : Jurnal Pertanian dan Peternakan, 2019)
This research intent to know diversifies Sago Product (Metroxylon sp) and local alimentary consumption pattern Papua original society coast at Makimi village, Makimi district, Nabire's regency. Done by approaching kualitatif' method, and this research type gets descriptive character. Data that is utilized in this research is primary and secondary data with observational location at Makimi village, up to 4 months, June until September 2018. Analisis is data did by Triangulation method, which is interview, observing and documentation method. Result This research to point that pattern consumes original society local food Papua coast of sago product was changed. Food of sago product that formerly as alimentary as Papua original society subjects Coast are now more at dominate by rice. Changing it is regarded too by its reducing sago product at traditional market. This research also points out that that change regarded by diversified food product of sago raw product.